RAPD, ISSR and RFLP fingerprints as useful markers to evaluate genetic integrity of micropropagated plants of three diploid and triploid elite tea clones representing Camellia sinensis (China type)and C. assamica ssp. assamica (Assam-India type) - Devarumath, R. M.; Nandy, S.; Rani, V.; Marimuthu, S.; Muraleedharan, N.; Raina, S. N.
An efficient in vitro propagation method using enhanced axillary branching cultures produced plants from nodal explants of three mature, elite tea clones: diploid UPASI 26 and UPASI 27 (2n=2x=30)representing Camellia sinensis (China type)and triploid UPASI 3 (2n=3x=45)representing C. assamica ssp. assamica (Assam- India type). The genetic fidelity of the micropropagated plants of these three tea clones was assessed by analysing their nuclear, mitochondrial (mt), and chloroplast (cp)genomes using multiple molecular DNA markers. A total of 465, 446 and 462 genetic loci were produced with RFLP, RAPD and ISSR fingerprinting in the micropropagated plants and the corresponding mother plant of C. sinensis clone U (UPASI)26, and C. assamica ssp. assamica clones U3 and U27, respectively. RFLP fingerprinting was performed using six restriction endonuclease digests and 14 mt and cp gene probes in 84 enzymeprobe combinations. For PCR fingerprinting, 50 RAPD and SSR primers were used for amplifications. The micropropagated plants of both the U3 and U27 clones revealed complete stability in the 462 and 446 genetic loci analysed. In comparison, 36 (7.7
Keywords: CAMELLIA SINENSIS (CHINA TYPE); CAMELLIA ASSAMICA SSP. ASSAMICA (ASSAM-INDIA TYPE); ENHANCED AXILLARY BRANCHING; MOLECULAR DNA MARKERS; SOMACLONAL VARIATION